-39 - (+26) = -39 - 26 = -65
-17
39 minus -20/6 is 42 1/3
The first four positive integers of 13 are : 26, 39, 52, 65
52 minus 26 is 26.
-39 - (+26) = -39 - 26 = -65
-39 minus -26 is -13
39 - - 26 = 65
39.
-17
39 minus -20/6 is 42 1/3
A minus by a minus by a positive gives a positive.
The first four positive integers of 13 are : 26, 39, 52, 65
52 minus 26 is 26.
A minus plus a minus is not necessarily positive. A minus multiplied by a minus is. The reason being that the minus of a minus is a positive. It's a double negative.
72-200-39 is equal to -167.
Because "minus a negative" is tha same as "plus a positive". So, a positive minus a negative is a positive plus a positive which is a positive.